The Role of Wives as Family Breadwinners: An Islamic Legal and Sociological Perspective - Muh. Baehaqi; Nur Aziz; Nashih Muhammad (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
This study examines the phenomenon of wives assuming the role of family breadwinners in Muncar Village, Gemawang District, Temanggung Regency, from the perspectives of Islamic law and sociology. The research is motivated by empirical realities in which wives undertake economic responsibilities due to husbands’ inability to provide financial support as a result of prolonged illness, unemployment, advanced age, or unstable employment. Employing an empirical legal research design with a qualitative approach, data were collected through field observations and in-depth interviews with wives who function as primary income earners.The findings reveal that wives engage in diverse occupations, including agricultural labor, factory work, civil service, and domestic employment, to sustain household economies. From an Islamic legal perspective, the study finds that wives’ participation in income-generating activities is permissible, provided that it does not negate their primary responsibilities in managing household affairs and nurturing children. Such practices are consistent with the principles of mutual cooperation (ta‘āwun), responsibility, and compassion as emphasized in the Qur’an, the Sunnah, and the Compilation of Islamic Law. From a sociological perspective, the shift in wives’ roles reflects broader processes of social change driven by economic pressures, rising living costs, and the need to secure children’s education and family welfare.This study concludes that the role of wives as breadwinners in Muncar Village represents an adaptive social strategy that reconciles religious norms with contemporary socio-economic realities. While the obligation of financial provision remains primarily with the husband under Islamic law, wives’ economic participation emerges as a pragmatic and socially inevitable response to structural constraints, reinforcing family resilience without undermining Islamic legal principles.